Wild Horse Springs - Thomas, Jodi (Thomas, Jodi. Ransom Canyon romance., 2017)
Dan Brigman may not lead the most exciting life, but he's proud of what he's achieved: he's a respected lawman, and he's raised a bright, talented daughter on his own. But finding a lone, sparkly blue boot in the middle of a deserted highway gets him thinking maybe the cowgirl who lost it is exactly the shake-up he needs. After losing her baby girl, Brandi Malone felt like her soul died along with her daughter. Now singing in small-town bars to make ends meet, she's fine being a drifter<U+2014>until a handsome sheriff makes her believe that parking her boots under his bed is a better option. College grad Lauren Brigman has just struck out on her own in downtown Dallas when a troubling phone call leads her back home to Crossroads. Her hometown represents her family, friends and deepest hopes, but also her first love, Lucas Reyes. Will Lauren's homecoming be another heartbreak, or a second chance for her and Lucas?